PEMECAHAN EMULSI DENGAN METODE PENGGARAMAN PADA SLUDGE HEAVY PHASE - , VINDIANA SEPTRI ARYUNINGTYAS; , Dra. Ani Setyopratiwi, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research of emulsion breaking with salting method in sludge heavy phase has been done. The purpose of this study was to determine the effect of NaCl toward the emulsion stability, determining the critical micelle concentration (CMC) point, and optimizing the amount of NaCl (weight % b/b) to produce the optimum of palm oil that can be separated. Separation of the oil contained in the sludge heavy phase was conducted by extraction method using nâhexane as a solvent. The electrical conductivity (DHL) of the sludge was measured to determined the CMC point. The chemical and physical properties of the oil were analyzed including free fatty acid (FFA), water content, peroxide value, spesific weight, viscosity, and colour. The fatty acid composition of the oil was analyzed using GCâMS method. The results showed that the NaCl could break the emulsion. The CMC point was achieved at levels of 10 wt.% NaCl. The optimum NaCl ammount was 10 wt.% with oil recovery of 0.21 wt.%. The palm oil showed the FFA value of 0.29%, the water content was not detected, and specific weight of 0.91 g/mL (followed the SNI 01â2901â2006). The oil has a yellowish color. The peroxide value and viscosity was 5.43 meq/g and 62.1 centipoise (did not followed the SNI 01â2901â2006). The results of GCâMS analysis showed that the composition of free fatty acid in palm oil was palmitic acid, stearic acid, and oleic acid of 31.88%, 30.14%, and 23.91%, respectivelly.